THE SPIRIT, JUSTICE AND BEAUTY? (Acta Theologica)
In this article I want to make four interrelated arguments. Firstly, I argue for the theologically important relation between justice and beauty; secondly, that the Spirit of God is the Spirit both of “justice” and of “beauty”; thirdly, that a theology of the Spirit further defines “justice” and “beauty” and allows for a deepened understanding of both; and fourthly, that a theology of the Spirit allows us to understand the ambiguities with regards to these differentiated themes – and therefore highlights not only the importance of the interrelation between “beauty” and “justice” – but, I argue, is this interrelation. I will do this by focusing on the issue of how the Spirit relates, in the first place, to justice, in the second place, to creation, thirdly, to creativity and in the fourth place, to imagination.